2013
DOI: 10.1016/j.jobcr.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of fracture resistance of various post systems using different luting agents under tangential loading

Abstract: Within the limitations of this in vitro study, it can be stated that fibre posts can be recommended as a better alternative to the cast post and cores and prefabricated metallic posts in the anterior region and resin cement might give additional fracture resistance when used for post and crown cementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Some studies reported ETT restored with fiber posts have better fracture resistance than titanium posts. 2,3,7 Opposite findings have also been reported. [15][16][17][18][19][20][21][22] Meanwhile, some studies concluded no significant difference between the two post materials.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Some studies reported ETT restored with fiber posts have better fracture resistance than titanium posts. 2,3,7 Opposite findings have also been reported. [15][16][17][18][19][20][21][22] Meanwhile, some studies concluded no significant difference between the two post materials.…”
supporting
confidence: 54%
“…Another reason might be the loss of pulpal proprioception. 3 Therefore, restoration after endodontic treatment is needed to replace the missing hard dental tissues and provide the necessary strength to ETT, restoring tooth function. 4,5 Full crown coverage is commonly used to restore ETT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…33 Like the literature reviews, laboratory and finite element studies have also cited the differences between failures in retainer systems and have shown that the greatest numbers of non-catastrophic failures are in fiberglass posts when compared with cast metallic cores, justifying the results where minor stresses are generated at the root when the fiberglass post is used, reducing the chance of the occurrence of root fracture, different from the higher fracture rates with cast metallic cores. 15,38,39 These results of lower catastrophic failure rates for the fiberglass post are associated with the lower elastic modulus, as the fiberglass posts are more similar to dental structures than are metal retainers. 39 This elastic modulus, which is similar to that of dentin, generates a better load distribution throughout the system; therefore, the fracture resistance is smaller than in metallic cores, 16 and the fiberglass post shows a more favorable biomechanical behavior.…”
Section: Discussionmentioning
confidence: 95%